Pengaruh Permainan Sirkuit Akar Pensil Terhadap Hasil Belajar Gerak Dasar Pencak Silat Kelas V SD - Aji, Febri Wasono; Indahwati, Nanik (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to determine the effect of the pencil root circuit game on the learning outcomes of the basic movements of Pencak silat. This study used an experimental method with a one group pretest-posttest design. The research was conducted by practicing the movements of the easel, step patterns, punches, and kicks in martial arts material. The subject or sample of this study was grade V elementary school students with a total of 24 students. Data collection techniques use purposive samples and are analyzed using quantitative descriptions and difference tests. The results of this study show that using pencil root circuit games can improve students' abilities in terms of stance, step patterns, punches, and kicks on martial arts material. There is an increase because the game can foster students' willingness to do something to be more than before. Conclusion, there is an influence of pencil root circuit games on the learning outcomes of basic pencak silat movements of grade V elementary school students. Keyword : Basic Pencak Silat Motion, Circuit Game, Elementary School